Body, heart, thyroid gland and skeletal muscle weight changes in rats with altered thyroid status - Soukup, T; Zacharová, G; Smerdu, V; Jirmanová, I (Physiological research, 2001)
In the present paper we describe changes of anatomical parameters in inbred Lewis strain rats, namely their body weight, body weight gain per week, absolute and relative heart, thyroid gland and skeletal muscle weights, that are assumed to reflect experimentally altered thyroid status. The hyperthyroid state was induced by DL-thyroxine or Na 3,3',5-triiodo-L-thyronine, while methimazole was employed for inducing hypothyroidism. We have found that when compared to euthyroid rats, hypothyroidism resulted in a significantly lower body weight gain, absolute and relative heart weight and, in contrast, in a significant increase of absolute and relative thyroid gland weight. On the other hand, hyperthyroidism led to a significant increase of absolute and relative heart weight and to a significant reduction of absolute and relative thyroid gland weight. However, the body mass was not significantly altered in hyperthyroidism as compared with euthyroid rats. We conclude that our protocol leads to chronic hyper- or hypothyroidism as demonstrated by body, heart and thyroid gland weight changes. These anatomical data can thus be utilized as supplemental criteria for the assessment of the thyroid state of experimental rats.
Keywords: Animals; kosterní svaly; potkani inbrední LEW; Female; ženské pohlaví; Organ Size; Muscle, Skeletal; Hyperthyroidism; Hypothyroidism; tělesná hmotnost; velikost orgánu; štítná žláza; hypertyreóza; Thyroid Gland; krysa rodu Rattus; Body Weight; zvířata; Myocardium; myokard; Rats, Inbred Lew; Rats; hypotyreóza